2022
DOI: 10.3389/fmed.2022.882335
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Prospective, Randomized, Single Blind, Cross-Over Study on the Effect of a Fixed Combination of Citicoline 500 mg Plus Homotaurine 50 mg on Pattern Electroretinogram (PERG) in Patients With Open Angle Glaucoma on Well Controlled Intraocular Pressure

Abstract: PurposeTo evaluate the potential beneficial and synergistic effects of oral intake of a fixed combination of citicoline 500 mg plus homotaurine 50 mg (CIT/HOMO) on retinal ganglion cell (RGC) function in subjects with glaucoma using pattern electroretinogram (PERG) and to investigate the effects on visual field and quality of life.MethodsConsecutive patients with primary open-angle glaucoma with controlled IOP (<18 mmHg) receiving beta-blockers and prostaglandin analogs alone or as combination therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…In addition, another randomized, controlled, multicentric trial showed that daily oral administration of a fixed combination of citicoline and homotaurine for four months improved inner retinal cell function. Moreover, the visual field and the perception of quality of life were both positively affected by this improvement, which happened independently of IOP decrease [66] (Table 2). For this reason, homotaurine could be considered a potential neuroprotective compound that could reduce RGC loss thanks to its cytoprotective and neurotropic properties, helping in the management of glaucoma.…”
Section: Homotaurinementioning
confidence: 92%
“…In addition, another randomized, controlled, multicentric trial showed that daily oral administration of a fixed combination of citicoline and homotaurine for four months improved inner retinal cell function. Moreover, the visual field and the perception of quality of life were both positively affected by this improvement, which happened independently of IOP decrease [66] (Table 2). For this reason, homotaurine could be considered a potential neuroprotective compound that could reduce RGC loss thanks to its cytoprotective and neurotropic properties, helping in the management of glaucoma.…”
Section: Homotaurinementioning
confidence: 92%
“…In another study, a randomized controlled multicentric trial demonstrated that the daily oral intake of the fixed combination of citicoline and homotaurine for 4 months led to an improvement in the function of inner retinal cells. This improvement occurred independently of intraocular pressure (IOP) reduction and positively impacted both the visual field and the perception of quality of life [27].…”
Section: Homotaurinementioning
confidence: 99%
“…There is clinical evidence that citicoline improves visual acuity in patients with amblyopia [ 771 - 786 ], visual function in patients with glaucoma [ 787 - 814 ], in patients with non-arteritic ischemic optic neuropathy [ 815 , 816 ], and in early diabetic retinopathy [ 817 ].…”
Section: Clinical Experiencementioning
confidence: 99%
“…Existen evidencias clínicas de que la citicolina mejora la agudeza visual en pacientes con ambliopía [ 771 - 786 ], la función visual en pacientes con glaucoma [ 787 - 814 ], en pacientes con neuropatía óptica isquémica no arterítica [ 815 , 816 ] y en la retinopatía diabética temprana [ 817 ].…”
Section: Experiencia Clínicaunclassified